2022
DOI: 10.3390/en15134785
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Urban Development on Regional Green Development Efficiency—A Case of the Yangtze River Delta in China

Abstract: Green development is a significant concept that cannot be ignored in contemporary society. However, in the context of China’s transition from high-speed growth to high-quality development, the complex impact of urban development has brought great challenges to the urban green environment. In this paper, the impact of urban development on green development efficiency (GDE) was studied. First and foremost, a Super-SBM model was introduced to measure the GDE of 41 cities in the Yangtze River Delta during 2009–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The increase of impervious area and the reduction of the green area have seriously caused problems for the water environment and atmospheric environment in cities [22,42]. On the contrary, in terms of geographic space, cities surrounded by mountainous terrain and famous for tourism enjoy high GDE as large-scale construction may not be applicable, such as Xuancheng, Huangshan, Quzhou and Jinhua, which is consistent to the conclusion of Li et al (2022) [40].…”
Section: Sfa Regression Analysissupporting
confidence: 53%
See 2 more Smart Citations
“…The increase of impervious area and the reduction of the green area have seriously caused problems for the water environment and atmospheric environment in cities [22,42]. On the contrary, in terms of geographic space, cities surrounded by mountainous terrain and famous for tourism enjoy high GDE as large-scale construction may not be applicable, such as Xuancheng, Huangshan, Quzhou and Jinhua, which is consistent to the conclusion of Li et al (2022) [40].…”
Section: Sfa Regression Analysissupporting
confidence: 53%
“…necessary to comprehensively consider the factors affecting GDE from various aspects [40]. Based on the spatial distribution maps drawn from the actual GDE results, the GDE in the YRD showed certain spatial heterogeneity, not only different from the conclusion of Wang et al (2018) who calculated that the GDE is low in the east and high in the west of the YRD [37], but also different from the conclusion of Deng et al (2021) who found that the GDE in the eastern region is significantly higher than that in the western region [39].…”
Section: Gde Analysis In the Yrdmentioning
confidence: 99%
See 1 more Smart Citation
“…New models for green production, living, and consumption patterns were actively promoted, alongside green economic transformation. Priority was given to guiding all people to participate in the construction of green travel, ecology, and resource-saving and environment-friendly urbanization development mechanism (Li et al, 2022). Furthermore, each 1% increase in EU in neighboring cities resulted in a 0.195%, 0.042%, and 0.206% increase in local city's IEE, PTE, and SE, respectively.…”
Section: Spatial Interactive Effects Between Eu and Ieementioning
confidence: 99%
“…Recent literature indicates that foreign direct investment (Wang, 2020; Zhu & Ye, 2018), fiscal decentralization (Song et al, 2018), green finance (Desalegn & Tangl, 2022), the digital economy (Ren et al, 2022; Xiang et al, 2022), land and finance misallocation (He & Du, 2022; Li, Shangguan, et al, 2022), knowledge production capacity (Cooper et al, 2020), economic development (Li et al, 2021), economic policy uncertainty (Gu et al, 2021), technological change and progress (Chen et al, 2020; Sun et al, 2020), the integration of technology and efficiency (Guan et al, 2022), and economic system reform (Schoneveld & Zoomers, 2015) influence inclusive green growth. Meanwhile, industrial structure upgrading, trade openness, human capital, and urban innovation may positively influence inclusive green growth, while government intervention and industrialization would have a negative effect (Fan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%